MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MODEL KOOPERATIF TIPE STAD BERBANTUAN MEDIA TAKALINTAR PADA MATERI OPERASI PERKALIAN BILANGAN CACAH KELAS IV SDN 14 BONGOMEME - Dewi Asih, Ni Nyoman; Irvin Novita Arifin; Andi Marshanawiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT Low student learning outcomes in mathematics learning, especially in whole number multiplication operations. This research aims to improve students' mathematics learning outcomes through the STAD type cooperative model assisted by takalintar media in the material on the operation of multiplication of whole numbers for class IV SDN 14 Bongomeme. This type of research is Classroom Action Research (PTK). The results of research from 16 students showed that in cycle 1 the learning outcomes of students who reached the minimum completeness criteria were 9 students with a percentage of 56%. This result has not yet reached the specified performance indicator criteria, namely 80%, so it is continued in the next cycle, namely cycle 2. In cycle 2, 14 students achieved the minimum completeness criteria with a percentage of 88% and had achieved the specified performance indicator criteria. Keywords: learning outcomes, STAD type cooperative model, takalintar media ABSTRAK Rendahnya hasil belajar siswa pada pembelajaran matematika khusunya materi operasi perkalian bilangan cacah. Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa melalui model kooperetif tipe STAD berbantuan media takalintar pada materi operasi perkalian bilangan cacah kelas IV SDN 14 Bongomeme. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Hasil penelitian dari 16 siswa menunjukkan bahwa pada siklus 1 hasil belajar siswa yang mencapai kriteria ketuntasan minimal sebanyak 9 siswa dengan persentase 56%. Hasil ini belum mencapai kriteria indikator kinerja yang ditetapkan yakni 80%, sehingga dilanjutkan pada siklus selanjutnya yakni siklus 2. Pada siklus 2 siswa yang mencapai kriteria ketuntasan minimal sebanyak 14 siswa dengan persentase 88% dan telah mencapai kriteria indikator kinerja yang telah ditetapkan. Kata Kunci: hasil belajar, model kooperatif tipe STAD, media takalintar